Mechanics of bacteria-assisted extrinsic healing. (June 2020) - Xin, An; Du, Haixu; Yu, Kunhao; Wang, Qiming
Abstract: Self-healing materials can typically be divided into two types: intrinsic healing that harnesses dynamic bones to autonomously repair fractures, and extrinsic healing that uses the externally added components to enable the bonding of fractured interfaces. Although the theoretical modeling of intrinsic self-healing materials has been recently studied by Wang et al., the fundamental understanding and theoretical modeling of the extrinsic self-healing materials remain elusive. Without a deep understanding of the extrinsic healing mechanics, the design of extrinsic-healing materials and corresponding applications are still at the trial-and-error stage. Here, taking bacterial-precipitation-enabled healing as an example, we construct a modeling framework to explain the bacteria-assisted extrinsic healing mechanics. A model for the growth of crystal pillars is developed to explain the bacteria-assisted growth of the calcium carbonate (CaCO3 ) crystal forest within the fracture interface, and a cohesive zone model is built to explain the interfacial bonding. Our modeling framework can explain the evolution of the interfacial healing strength over the healing time and reveal the effects of interface distance and concentrations of bacteria and calcium ions on the healing performance. The modeling results are consistent with the bacteria-assisted healing experiments of ceramics and cement.